Urologic Morbidity in Surgery of Placenta Accreta Spectrum in Universitas Andalas Hospital - Zulfiqar Yevri (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Hysterectomy for placenta accreta spectrum disorders is known to be associated with urologic morbidity, including intentional or unintentional cystostomy, ureteral injury, and bladder fistula. Case: A 32year old woman with urine retention post total hysterectomy on indications placenta accreta spectrum Grade 3 type 4 S2 segment- 9 days ago, referred to Universitas Andalas Hospital. The patient complained difficulty to urinate, hematuria and supra pubic pain. Physical examination sign of acute abdomen unclear. A Pelvic abdominal ultrasound was performed, the result were Acites and complex acites, left renal hydronefrosis, cystitis and sludge gallblader. From the laboratory result found anemia, leucocytosis, trombositosis, ureum, creatinine and albumin were in normal limit, hyponatremia, hypokalemia, hypocalsemia. The patient were given antibiotics, blood transfusion and natrium, kalium and calcium correction. Cystoscopy was performed to explore the bladder, the result were found adhesion and ruptured at the posterior wall of the bladder a long 3 cm then proceed with laparotomy to repair the bladder and adhesiolisis. During hospitalization, the patient’s condition was good, hemodynamics was stable with sufficient diuresis. The patient was discharged on day 4 after laparotomy of bladder repair with temporary urine catheter installed. Discussion: This patient diagnose previously is placenta accreta spectrum with percreta graded so had a high risk of urologic morbidity. The bladder ruptured occurred after 9th day of hysterectomy. This can occur because the injury during dissection of the uterine vesicular fold undergoes necrosis and then become opens on the 9th day after hysterectomy. A multidisciplinary team should be made in management of placenta accreta spectrum. A team comprising a consultant maternal fetal medicine with pelvic surgery experienced, a blood bank team, an anesthesiologist, a urologist skilled, an interventional radiologist and an experienced neonatologist is advised. Keywords: urologic complication, placenta accreta, urologic morbidity